2007
DOI: 10.1001/archinte.167.8.802
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Association Between Depressive Symptoms and Incident Type 2 Diabetes Mellitus in Older Adults

Abstract: Background: Prospective studies indicate that a single self-report of high depressive symptoms is associated with an increased risk of developing type 2 diabetes mellitus. Methods: We tested whether a single report of high depressive symptoms, an increase in depressive symptoms, or persistently high depressive symptoms over time were associated with the development of diabetes in adults 65 years and older. Participants from the Cardiovascular Health Study completed the 10-item Center for Epidemiological Studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
95
2
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(106 citation statements)
references
References 36 publications
7
95
2
2
Order By: Relevance
“…In contrast to other studies [2][3][4], our results do not indicate that depression is a causal risk factor for diabetes. Our study design differed in two aspects from these studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to other studies [2][3][4], our results do not indicate that depression is a causal risk factor for diabetes. Our study design differed in two aspects from these studies.…”
Section: Discussioncontrasting
confidence: 99%
“…First, depression and psychosocial complaints might be risk factors for diabetes. Indeed, several previous longitudinal studies have shown that depression increased the risk of developing diabetes [2][3][4]. Second, antidepressants themselves might be a risk factor for diabetes, as the literature indicates that antidepressant use can disturb glucose levels and glycaemic control [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the prevalence of overweight and obesity has increased in the United States and worldwide, it is important to track ORCs including mental disorders, which could further exacerbate the course and outcomes of physical morbidities and ultimately result in disability or impaired health-related quality of life. 24,[58][59][60] Indeed, public health intervention programs aimed to attain an ideal body weight or BMI in the population could beneficially affect both physical and mental health status. …”
Section: Discussionmentioning
confidence: 99%
“…Only two of the studies in this review measured inflammatory factor levels (12,32); neither of them reported the individual effect of inflammatory factor levels on the risk of diabetes, because both studies were concerned with the effect of depression on the development of diabetes. Published reviews have suggested a PSR model to explain the link between depression and diabetes, but the reviewers report that there is little research to support this model (22), and the role of antipsychotic medication on glucose metabolism is unclear (29).…”
Section: Discussionmentioning
confidence: 99%